Wiersze pochwalne na cześć Elżbiety z Branickich Sapieżyny i jej najbliższych krewnych - Dąbrowski, Szymon Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The paper is devoted to occasional laudatory verses which were written to honour princess Elżbieta Sapieżyna (née Branicka) and the members of her closest family – son Kazimierz Nestor Sapieha, General of the Lithuanian Artillery and brother Franciszek Ksawery Branicki, Great Crown Hetman. The begining of the article reminds of already known literary works containing complimentary images of the female aristocrat. The main object of author’s interest are pieces that have not been noticed by scholars of the eighteenth-century political writings. These are: anonymous ode written in 1784 in connection with arrival of Sapieżyna to Prienai (pol. Preny) in Lithuania and collection of four verses created by Wojciech Zacharkiewicz, who thereby added splendour to the Franciszek Ksawery Branicki’s coming to Warsaw for parliamentary sitting of the Great Sejm and to election of Kazimierz Nestor Sapieha for the Marshal of lithuanian confederation. The author discussed circumstances of the creation, main motifs of content and artistic composition of laudatory images of addressees. Furthermore he determined connections of these verses with then popular genres of occasional poetry and put Sapieżyna’s complimentary portraits in context of manners of creation women’s images in literary works of that time.